2010
DOI: 10.1074/jbc.m110.147199
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Requirements for the Insecticidal Activity of the Plant Peptide Pea Albumin 1 Subunit b (PA1b)*

Abstract: PA1b (pea albumin 1, subunit b) is a small and compact 37-amino acid protein, isolated from pea seeds (Pisum sativum), that adopts a cystine knot fold. It acts as a potent insecticidal agent against major pests in stored crops and vegetables, making it a promising bioinsecticide. Here, we investigate the influence of individual residues on the structure and bioactivity of PA1b. A collection of 13 PA1b mutants was successfully chemically synthesized in which the residues involved in the definition of PA1b amphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 33 publications
6
50
0
Order By: Relevance
“…Like kB1 (33), PA1b recently has been demonstrated to be highly tolerant to modification outside the cystine knot core (32). This observation supports the possibility of divergent evolution of cyclotides from ancestral albumin domains.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Like kB1 (33), PA1b recently has been demonstrated to be highly tolerant to modification outside the cystine knot core (32). This observation supports the possibility of divergent evolution of cyclotides from ancestral albumin domains.…”
Section: Discussionsupporting
confidence: 68%
“…SPR studies done here show that Cter M interacts with membrane lipids, a mechanism common to other cyclotides, which appear to not have stereospecific receptors and are instead pore-forming membrane disruptors (34). In contrast, PA1b interacts specifically with a membrane-based receptor in insect cells (32).…”
Section: Discussionmentioning
confidence: 94%
“…The absence of any effect of PA1b when directly applied to the inside of the cell corroborates previous results showing that PA1b is internalized in Sf9 cells but that it has an effect only when the toxin is localized outside of the cell (17). However, the most important observation is the absence of any effect of the F10A mutant, which was demonstrated as being without toxicity and without any indication of binding to the PA1b receptor (20). Hence, it is clear that the reported effect of PA1b in blocking an ionic current is very specific to the PA1b structure, and this could underlie its toxicity.…”
Section: Discussionsupporting
confidence: 71%
“…The F10A mutant was obtained by chemical synthesis according to the method described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the pea albumin-1 subunit-b (PA1b), one of the best-studied Fabaceae albumin components, is a 37-aa peptide from pea seeds (Pisum sativum), which also contains a cystine-knot structure (13). Remarkably, the cystine-knot core of PA1b overlays extremely well with that of the cyclotide Cter M. The composition and size of the PA1b loops are, however, totally different from those of the cyclotide Cter M. Recent mutagenesis studies on PA1b have also recently shown that this albumin domain is highly tolerant to mutations outside the cystine knot core (14). These observations support the possibility of divergent evolution of cyclotides from ancestral albumin domains, wherein evolution and natural selection provided an alternative loop decoration of the original cystine knot albumin core.…”
mentioning
confidence: 96%